Peningkatan hasil belajar pola bilangan melalui pembelajaran numerasi dengan kegiatan Meronce - Farah, Zahida; Rohimah, Siti Maryam; Fitria, Amie (Universitas PGRI Semarang, 2025)
Mastering number pattern material at the elementary school (SD) level is not just about understanding the sequence of numbers. Still, it is an essential foundation in developing mathematical thinking, logic, and problem-solving skills that will be useful throughout their education and daily lives. However, many students still have difficulty learning number patterns. Therefore, learning is needed to help students understand the material more easily, including numeracy with beading activities. This study aims to improve the learning outcomes of students' number patterns through numeracy in beading activities in grade IV of elementary school. This study uses a case study method with a descriptive qualitative approach to see the application of beading activities as a contextual and enjoyable learning medium. The research subjects consisted of 26 grade IV students of SDN 111 Pindad, Bandung City. Based on the diagnostic assessment results, students are divided into two categories of different ability levels. The category of developing students is 17 people, and the category of students needing guidance is nine. Data collection techniques in this study are evaluation questions, observation sheets, and documentation. Data were analyzed using instrument validity, data collection, data reduction, data presentation, and the conclusion-drawing stage. The study results showed that the average evaluation score of students who developed was 83, and the average evaluation score of students who needed guidance was 80. Stringing activities involving manipulating concrete objects can help students understand number patterns more easily. Therefore, numeracy learning through stringing activities has been proven effective in improving students' learning outcomes on number pattern material and providing a fun learning experience. This study suggests using manipulative-based methods in mathematics learning to create a more interesting and meaningful atmosphere for students.